ISHLAB CHIQARILGAN MAHSULOT TANNARXI TO‘G‘RISIDAGI HISOBOTI - Xudaynazarova Dilnoza; Abduahadov Samandar (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article examines the preparation of the report on the cost of manufactured products, focusing on both theoretical and practical aspects. The study analyzes the concept of product cost, its economic essence, and its role in accounting. It also considers the classification of production costs and the principles of including them in the cost of production. The article describes in detail the methods of calculating product cost, the stages of its formation, and the procedure for preparing cost reports. The application of the weighted average method and other costing methods is also analyzed in practice. The results of the study show that the cost of production report plays an important role in determining financial results, controlling expenses, and supporting managerial decision-making in enterprises.